Reactogenicity Profile of Health Workers Recipients of Heterologous mRNA Boosters Vaccine at Arifin Achmad Hospital (Nusantara Science and Technology Proceedings, 2022)
Coronavirus disease (COVID-19) is an infectious disease that has been designated by the World Health Organization (WHO) as a global pandemic. There are different types of COVID-19 vaccines that have been developed. Reactogenicity is a reaction that occurs immediately after vaccination. Differences in individual immune responses against antigens can trigger local and systemic reactions. Medical events due to immunization are known as Adverse Event Following Immunization (AEFI). The purpose of this study was to determine the reactogenicity profile of health workers receiving the heterologous mRNA (Moderna) booster vaccine at Arifin Achmad Hospital. This study was a cross-sectional study to determine the Adverse Event Following Immunization (AEFI) of health workers receiving heterologous mRNA booster vaccines (Moderna) at Arifin Achmad Hospital. Respondents in this study were mostly women (63.2%), aged 30-39 years (42.5%), overweight (50.6%), had no comorbid disease (74.7%) and were not survivors of COVID -19 (86.2%). From a total of 87 respondents, there were KIPI in the form of general complaints of fever/chills in 70 respondents (80.5%), swelling in the injection area in 44 respondents (50.6%), muscle pain in 72 respondents (82.8%), decreased/increased appetite 17 respondents (19.5%), often sleepy/sleep longer 14 respondents (16.1%), numbness in hands and/or feet 8 respondents (9.2%), nasal congestion 11 respondents (12.6%), and cough 6 respondents (6.9%).